Urgensi Implikasi Green Constitution Dalam Mewujudkan Sustainability Green City - Aisya Yube, Rihhadatul; Algifary, Ghazy; Meisya Adriani, Nabilla (Fakultas Hukum Universitas Andalas, 2025)
Environmental degradation in Indonesia requires strong and integrated legal protection. This study examines the urgency of implementing the Green Constitution as a legal foundation for sustainable green city development. The research employs a normative juridical method with statutory and conceptual approaches through literature review of regulations, jurisprudence, and scholarly works. The findings reveal that although the Green Constitution is not explicitly regulated, its substance is embedded in Articles 28H and 33 of the 1945 Constitution as well as Law No. 32 of 2009 on Environmental Protection and Management. Implementation challenges include weak law enforcement, regulatory conflicts, and low public awareness. This study recommends strengthening legal instruments at both national and local levels, harmonizing policies, and fostering cross-sector collaboration so that the Green Constitution can serve as a strategic foundation for achieving equitable, sustainable green city development. Keywords : Environmental Law, Green constitution, Sustainability Green City